Analisis Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian Dalam Memilih Mobil Bekas Di Wilayah Kartasura Sukoharjo - Cahyanto, Agung Dwi, Basworo Dibyo, SE., M.Si (2017)
The purpose of this study is 1) To analyze brand awareness affect the decision of buying used cars in the Kartasura Sukoharjo region. 2) To analyze the brand association affect the decision of buying used car in Sukoharjo Kartasura region. 3) To analyze the impression of quality affect the decision of buying used car in Sukoharjo Kartasura region. 4) To analyze brand loyalty affect the decision of buying used car in Sukoharjo Kartasura region The sampling technique used is non probability sampling with purposive sampling method while the sample is 100 respondents. Based on the results of the study note that the brand awareness variable has a significant influence on purchasing decisions. Brand association variables have a significant effect on purchasing decisions. Variables of quality impression have a significant influence on purchasing decision. The loyalty variable has a significant influence on the purchasing decision.